Traumatic Experiences In "Salt" Movie Directed By Phillip Noyce (2010): A Psychoanalytic Approach - Fauzi, Muhammad Amin (2012)
This research is proposed to analyze traumatic experiences in a film with title Salt using Psychoanalytic Approach. There are two objectives. The first is to analyze the film in term of structural analysis and the second is to analyze the film based on Psychoanalytic Approach. The research paper belongs to the qualitative research. The object of the study is the personality of Evelyn in Salt movie. There are two kinds of data sources used in this research, they are primary and secondary. The primary data is the film itself and the secondary data sources are biography of the author, books and internet. The technique of data collection in this research is summarizing, paraphrasing, and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis Based on the structural analysis it is evident that in this movie, Phillip Noyce wants to deliver a message that an experience should be a lesson in the future. The structural elements are related to each other and form a unity. Based on the psychological analysis, it is clear that in Salt movie Phillip Noyce describes a psychological phenomenon, in which the major characters Evelyn Salt has some traumatic experiences